Answer:
First number = 3
Second number = 7
Explanation:
Let one number be =
![x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k3ozza40nv61jy1offmxaxutrb6y1c3ly5.png)
Let other number be =
![y](https://img.qammunity.org/2020/formulas/mathematics/college/uw0b7dbqmfpakodpw1nh8u5h9nrcutx8vw.png)
"One number added to three times another number is 24" can be written mathematically as:
![x+3y=24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5i959773waoze98hkrbpahindhtnd8kygo.png)
Five times the first number added to three times the other number is 36 can be written mathematically as:
![5x+3y=36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xbqpd0fjo3xhrfey74l8l80wk0xyln7el6.png)
So, we have a system of equation as:
A)
![x+3y=24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5i959773waoze98hkrbpahindhtnd8kygo.png)
B)
![5x+3y=36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xbqpd0fjo3xhrfey74l8l80wk0xyln7el6.png)
Solving for
and
using elimination.
Multiplying equation A with -1 and adding it to B to eliminate
![y](https://img.qammunity.org/2020/formulas/mathematics/college/uw0b7dbqmfpakodpw1nh8u5h9nrcutx8vw.png)
would be
![-1(x+3y=24)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n003thbwbjf6japl2508sp61pkhpd9g91s.png)
![-x-3y=-24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/riwnb2uvmdjc65xs4kbl4kycamdyrawxr2.png)
would be
![-x-3y=-24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/riwnb2uvmdjc65xs4kbl4kycamdyrawxr2.png)
+
![5x+3y=36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xbqpd0fjo3xhrfey74l8l80wk0xyln7el6.png)
We have,
![5x-x+3y-3y=36-24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jhv6e8ki5rwy1evs1yzdkp6g8ti2y0l9gd.png)
Thus
is eliminated. Now, we can solve for
![x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k3ozza40nv61jy1offmxaxutrb6y1c3ly5.png)
![4x=12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/31gv0q66fzbkt06qwy1pvlyc63duq67yzt.png)
Dividing both sides by 4.
![(4x)/(4)=(12)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z0u52fdx4nrqsbigitzjonrvzx9iuumy1u.png)
∴
![x=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jmja0xwsmt4jtrinnsn2lhtcie4am0nxwn.png)
Plugging in
in equation A to solve for
![y](https://img.qammunity.org/2020/formulas/mathematics/college/uw0b7dbqmfpakodpw1nh8u5h9nrcutx8vw.png)
![3+3y=24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/clyqt5wro4p9h19rk6uye0ws6p11up6y6s.png)
Subtracting both sides by 3.
![3+3y-3=24-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x25akwmcd3f2ta7fd7cswuc8zf98qxka3l.png)
![3y=21](https://img.qammunity.org/2020/formulas/mathematics/middle-school/glxt1sncd4y0bvey5njyywiqa9jbnzxsc2.png)
Dividing both sides by 3.
![(3y)/(3)=(21)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yteirlxqg7bk5yuuspiqaiz66ijnz326a7.png)
∴
![y=7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gvf6itkqfb4zpyy2ztyz4u1g2am8udpvaz.png)
So, first number = 3
Second number = 7